Influence of strawberry tree (Arbutus unedo L.) fruit ripening stage on chemical composition and antioxidant activity - Oliveira, Ivo (2014)
Arbutus unedo is a widespread shrub with economic importance, derived from the use of its berries in the production of alcoholic beverages and in folk medicine. This work intends to evaluate for the first time the effect of fruit ripening stage on antioxidant activity, total phenolic content, fatty acid profile and tocopherol composition. Ripe fruits shown higher extraction yield (45.04±2.23%) when compared to other fruit ripening stages. By contrast, total phenol contents were higher in the unripe and intermediate stage of ripeness (108 and 111 mg GAES/g dry fruit, respectively, against 60 mg/g dry fruit when ripe). Ripe and intermediate fruits shown the lower EC50 values on the DPPH radicals (0.25±0.02 mg/mL) and reducing power assay (1.09± 0.05 mg/mL), respectively. A significant correlation was established between antioxidant activity and fruits ripening stage. Fatty acid profiles were very similar between the ripening stages, being alfa-linolenic, linoleic and oleic, the three major ones. Polyunsaturated fatty acids (PUFA) represent as much as 60% of the total fatty acids, with a highly favorable omega 3/omega 6 ratio. From the analysis of the vitamin E vitamers, the most important was γ-tocotrienol, with a clear reduction in the total free vitamin E content with ripening. These results highlight that the fruits of intermediate ripeness can be regarded important sources of biologically active compounds with a fatty acid profile rich in omega-3 PUFA, properly supplemented with high vitamin E amounts.